A Two-Phase Optimization Approach for Reducing the Size of the Cutting Problem in the Box-Production Industry: A Case Study - Mosallaeipour, Sam; Nazerian, Ramtin; Ghadirinejad, Mazyar (Springer International Publishing Ag, 2018)
In this study, the cutting problem as one of the main problems within the box-production industries is discussed. The cutting problem refers to the problem of dividing a piece of rectangular raw material, which is usually large, into smaller pieces to produce various products. Cutting problems are NP-hard problems. Numerous researches offering good solutions to these problems have been conducted over the past few years. In the present study, considering the complexity of the problem, a model reflecting the nature of the problem is proposed and a new two-phase solution approach is suggested. Utilizing the proposed method significantly reduces the size of the problem and simplifies the applicability of the solution approach in real life. Furthermore, to evaluate the efficiency and utilization of the proposed method, its application in a specific company is tested. Finally, the performance of the method is calculated and its use is compared with the company's traditional method.
Global Joint Conference on Industrial Engineering and Its Application Areas (GJCIE ) -- JUL 20-21, 2017 -- Vienna, AUSTRIA
Keywords: Material selection; Production planning; Cutting problem